Unending War: Combat Trauma in Joss Whedon’s "Firefly" - Aneta Kliszcz; Joanna Komorowska (Załącznik Kulturoznawczy)
The article discusses the long-term effects of combat trauma as portrayed in Joss Whedon’s Firefly series, focusing on the issues of trust, identity, and belonging. In doing so, it highlights the image of warrior and war in popular culture.